"No Fats, No Femmes, and No Blacks or Asians": The Role of Body-type, Sex Position, and Race on Condom Use Online. - Smith, Jesús Gregorio; Amaro, Gabriel (AIDS & Behavior, 2021)
Despite the promises to end HIV infection rates by 2030, several factors continue to contribute to rising HIV infection rates in sexual minority communities. In fact, the CDC predicts that more than half of gay and bisexual men of color will be infected in the coming years if an intervention is not staged. While much focus has been placed on PrEP access, less has been given to the social environment online, which many men who have sex with men use to find sexual partners. This environment, facilitated by the anonymity afforded to men online, is infected with anti-fat, anti-femme, anti-Black bias aimed at men constructed as less desirable and summed up in the phrase, "No fats, No femmes, and No Blacks or Asians." Considering this online environment and the fact that past research suggests a relationship between weight and condom use, sex position and condom use and race and condom use, the researchers test all three pairings as well as a fourth hypothesis predicting if men who embody all three variables are also more likely to go condom-less. Findings from the analysis were mixed with men with "ideal body types" (slim, athletic and muscular built) and bottom men being more likely to have bareback on their profiles for sex behavior while men of color were more likely than Whites to have safe sex only. Most strikingly, regardless of body-type, sex position, or HIV status, Whites were more likely to have bareback on their profiles.